Developing latent fingermarks on the surface of unfired ammunition by using time-of-flight secondary ion mass spectrometry - Lee, Charles (2021)
It is a statement widely agreed upon that the friction ridge detail on a finger is unique to each digit and to find two that are exactly alike, between any two humans, is highly improbable. For this reason, fingermarks are considered of great importance to the judicial system as a match between two marks can confirm a shared identity. Due to the potential for identification, attempts to improve development processes of fingermarks is an area of interest for many researchers. One area that has been scarcely investigated is the development of latent fingermarks on ammunition by using time of flight secondary ion mass spectrometry.